ADJUVANTS IN IMMUNIZATION WITH INFLUENZA VIRUS VACCINES - Friedewald, William F. (The Rockefeller University Press, 1944)
Subcutaneous inoculation, of PR8 allantoic fluid, or watery suspensions of the virus obtained from allantoic fluid by high-speed centrifugation or by elution after adsorption on red cells induced serum antibodies in experimental animals, which reached the highest levels within 2 weeks after inoculation and were gradually lost thereafter. The addition of killed acid-fast bacteria (Myco. tuberculosis or butyricum), paraffin oil, and a proprietary adsorption base (Falba) to form a stable water-in-oil emulsion of influenza virus suspensions greatly enhanced and maintained immunity and antibody response to the virus. These adjuvants provided a much more effective method of increasing antibody production to the virus than the use of concentrated preparations of virus alone. Paraffin oil and Falba without the acid-fast bacilli were less effective as adjuvants, although the antibody levels induced were higher than those produced by watery suspensions of the virus and were maintained at a constant level for at least 6 months. Myco. butyricum appeared to be more effective in producing antibodies against the virus than the tubercle bacilli in the emulsions of paraffin oil and Falba. Immunization with these adjuvants and suspensions of influenza virus obtained from allantoic fluid induced antibodies not only against the virus but against antigenic material contained in normal allantoic fluid, although the latter titers were considerably lower. A suspension of influenza virus (sedimented by high-speed centrifugation) and Myco. butyricum in sesame oil induced about four times as much antibody as when the virus was suspended in saline, in sesame oil alone, or in combination with typhoid bacilli.